The split time : economic philosophy for human flourishing in African perspective - Wariboko, Nimi, 1962- (Albany : State University of New York Press, 2022)
"Aims to construct an economic philosophy from indigenous African thought"-- Provided by publisher.
Religion, temporality and desire -- Destiny and desire: an ontology of human flourishing -- Temporality and desire -- Economy and destiny: a theory of agonistic communalism -- Pursuit of excellence and economic development -- Naija-dialectics: theory and methodology.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on December 20, 2022).
JSTOR
Keywords: Economics -- Philosophy; Philosophy, African; Économie politique -- Philosophie; Philosophie africaine; Economics -- Philosophy; Philosophy, African